Pengaruh Nilai Kapitalisasi Saham Syariah, Nilai Ukuran Perusahaan, Dan Inflasi Terhadap Pertumbuhan Ekonomi Pada Tahun 2016-2023 - Irmawati, Ayu; Panggiarti, Endang Kartini; Retnosari, Retnosari (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to empirically examine the effect of Sharia Stock Capitalization Value, Company Size Value, and Inflation on Economic Growth in 2016-2023, a case study on the Indonesian Sharia Stock Index (ISSI). The method used in this research is quantitative method. This study has a population of 202 companies listed in ISSI during 2016-2023. The sampling technique is to use purposive sampling, so that the total sample obtained is 32 companies. Data analysis using multiple linear regression analysis with the help of tools in the form of SPSS 26. The results of this study indicate that the variables of company size and inflation have a significant positive effect on economic growth. Meanwhile, the Islamic stock capitalization value variable has a negative and significant effect on economic growth. The conclusion of this study indicates that economic growth will increase if large companies can more effectively carry out social and economic responsibilities, thereby promoting inclusive and sustainable growth, and controlled inflation below ten percent. Meanwhile, Islamic stocks have a negative impact on economic growth due to the low level of public literacy regarding Islamic stocks. Keywords: Sharia Stocks, Firm Size, Inflation, Economic Growth